Interactive storytelling : 9th International Conference on Interactive Digital Storytelling, ICIDS 2016, Los Angeles, CA, USA, November 15?18, 2016, Proceedings /: 9th International Conference on Interactive Digital Storytelling, ICIDS 2016, Los Angeles, CA, USA, November 15?18, 2016, Proceedings. (2016) - Unknown
No abstract available